Controlled Internal Drug Release (CIDR) Based Hormonal Protocols Effect upon Estrus Response and Pregnancy Outcome in Anestrous Cows - Sah, A. K.; Pandeya, Y. R; Pathak, L. R; Gautam, G. (Nepalese Veterinary Journal, 2019)
Controlled internal drug release (CIDR) based hormonal protocols CoSynch + CIDR, OvSynch + CIDR and CIDR + PGF2α were applied to 25 crossbred anestrous Holstein and Jersey cows to improve the fertility at the farm of National Cattle Research Programme, Rampur, Chitwan. All three protocols were found equally effective (P>0.05) with 100% estrus expression rate, out of which, 80% (8/10), 85.7% (6/7) and 75% (6/8) had estrus expression with well cervix open at fixed time artificial insemination in CoSynch + CIDR, OvSynch + CIDR and CIDR + PGF2α protocols respectively and rest had estrus expression with partial cervix open. Statistically non-significant (P>0.05) pregnancy outcome that is 14.3 % (1/7) in CIDR+PGF2α group and 12.5 % (1/8) in OvSynch group while none in CoSynch + CIDR group were pregnant following fixed time artificial insemination. Poor pregnancy outcome of the anestrous cows in all protocols might not only have hormonal problem but also could have various other reasons which was beyond the objective of this research findings. Hence, study concludes anestrous cows respond well to the CIDR based hormonal protocols to revive the estrus.